2020
DOI: 10.1093/sleep/zsaa060
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate reduces nocturnal eating in sleep-related eating disorder

Abstract: Study Objectives Sleep-related eating disorder (SRED) is a parasomnia characterized by partial arousals from sleep with compulsive consumption of food with impaired level of awareness and memory for the event. Small case series’ have demonstrated efficacy of topiramate in SRED. We conducted a placebo-controlled randomized clinical trial of topiramate to assess efficacy in SRED. Methods Thirty-four participants with an ICSD-2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Treatment with topiramate was initiated in this case, given its documented benefit for controlling SRED in several reports 8 . Most notably, in a randomized control trial, SRED symptoms were significantly reduced with topiramate (74.7% to 33.2% nights/week; n=15) compared to placebo (77.0% to 57.4%; n=17) 9 .…”
Section: Discussionmentioning
confidence: 96%
“…Treatment with topiramate was initiated in this case, given its documented benefit for controlling SRED in several reports 8 . Most notably, in a randomized control trial, SRED symptoms were significantly reduced with topiramate (74.7% to 33.2% nights/week; n=15) compared to placebo (77.0% to 57.4%; n=17) 9 .…”
Section: Discussionmentioning
confidence: 96%
“…A new option may include selective serotonin reuptake inhibitors (SSRI), which have been beneficial in patients presenting with idiopathic SRED and depression [ 39 ]. Recently, a randomized, controlled study with topiramate for idiopathic SRED demonstrated a reduction of SRED symptoms; however, this study excluded participants on medications thought to contribute to the presence of SRED [ 40 ]. While there are several pharmacological options to treat SRED, treating underlying disorders and discontinuing precipitating drugs, like zolpidem, should be considered first.…”
Section: Discussionmentioning
confidence: 99%
“…Ac cord ing to the large co hort study, clonazepam ef fi cacy is 72.2%, while ef fective ness of zolpidem, fluoxetine, citalopram, mirtazapine, melatonin range be tween 58-78% [7]. Dif fer ent ap proach is ap pli ca ble for sleep-re lated eat ing dis or der since topiramate and sertraline were found to be ef fi ca cious in re duc ing night-time eat ing in pa tients with SRED [28]. More over, con vinc ing ev i dence proves that cir ca dian sleep-wake rhythm dis or ders could be cured with melatonin [11].…”
Section: Nrem Sleep Parasomniasmentioning
confidence: 92%